Regulatory insights into the production of UDP-N-acetylglucosamine by Lactobacillus casei - Rodríguez-Díaz, Jesús (Landes Bioscience, 2012)
UDP-N-acetylglucosamine (UDP-GlcNAc) is an important sugar nucleotide used as a precursor of cell wall components in bacteria, and as a substrate in the synthesis of oligosaccharides in eukaryotes. In bacteria UDP-GlcNAc is synthesized from the glycolytic intermediate D-fructose-6-phosphate (fructose-6P) by four successive reactions catalyzed by three enzymes: glucosamine-6-phosphate synthase (GlmS), phosphoglucosamine mutase (GlmM) and the bi-functional enzyme glucosamine-1-phosphate acetyltransferase/ N-acetylglucosamine-1-phosphate uridyltransferase (GlmU). We have previously reported a metabolic engineering strategy in Lactobacillus casei directed to increase the intracellular levels of UDP-GlcNAc by homologous overexpression of the genes glmS, glmM and glmU. One of the most remarkable features regarding the production of UDP-GlcNAc in L. casei was to find multiple regulation points on its biosynthetic pathway: (1) regulation by the NagB enzyme, (2) glmS RNA specific degradation through the possible participation of a glmS riboswitch mechanism, (3) regulation of the GlmU activity probably by end product inhibition and (4) transcription of glmU.